Analisis Pengaruh Biaya Fasilitas Terhadap Harga Jual Rumah Pada Perumahan Jenis Cluster Di Kota Pekanabru (Studi Kasus : Perumahan Harmoni Residence) - Vemby Mailino; Rian Trikomara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Construction and property business prospects in the city of Pekanbaru is still quite promising when viewed by 2011 the building sector/construction accounted for the largest Pekanbaru City Regional Income ie 27.71 % of the other sectors. As the economic development increase rapidly in Pekanbaru indirectly cause an increase of housing need that is no exception for the luxury housing for the middle and upper classes. Housing type of cluster to be one of the preferred type of luxury residential facility offers infrastructure, facilities and utilities are complete. In a facilities construction cost housing projects included in indirect costs, while the construction of housing units included in direct costs. The cost of the facility housing development project will be charged to the home buyer on the housing. In other words, the price paid by the buyer during the purchase of the house was added to the cost of construction of such facilities. In this study identified what are the facilities offered by the Residence Housing harmony and how much influence the cost of the facility to the price of the total cost of construction per each type of home. The results of this study have been identified as for the facilities offered by The Harmoni Residence cluster housing types are roads, drainage, club house, swimming pool, green garden, fountain, office management, shade trees, street lighting, garbage cans, doors gate (one gate system), as well as CCTV security post. As well known the availability of the facility , facility costs charged to the type of 65/112 is equal to 7.70%, type 105/154 of 5.59 %, and type 135/180 of 4.62 % of the selling price per house type . Keywords : Direct Cost , Indirect Cost , Cluster , Facilities , Housing